The role of cis- regulatory elements in abiotic- stress responses in plants - Ha, Chu Duc; Dung, Le Tien (Academia Journal of Biology, 2016)
Recent advances in plant biology research, particularly in genetic engineering, had provided new tools to mitigate food security caused by climate changes and rapid population growth. Cis-regulatory elements, usually located in the upstream of the promoter region, are the binding sites for transcription factors, and thus, control the expression of the gene. There are several important cis-regulatory elements, such as ABRE-involved in the abscisic acid responsiveness; MYBRS and MYCRS - drought responsive elements; DRE and LTRE - temperature responsive elements. Previous studies have shown the importance of cis-regulatory elements in stress-adaptation in plants. In this review, we summarized and discussed the roles of cis- regulatory elements in the adaptation of plants to abiotic stress and its application potential in development of stress-tolerant plants. Throughout the review, we showed that cis-elements could be parts of potential approaches for genetic engineering toward improved crop varieties. Furthermore, we also discussed the possibility to apply genome editing as a tool, such as CRISPR/Cas9 system, to redesign the cis-elements in the promoters of stress-responsive genes to generate “edited crops” with enhanced stress tolerance through modulating gene expression.